Food and agricultural policy for the 1980s - Johnson, D. Gale (Washington, D.C. : American Enterprise Institute, 1981)
This is a conference on Food and Agricultural Policy sponsored by the American Enterprise Institute. It was organized into three major groups of presentations. The first group included two papers, one concerned with economic developments affecting food and agriculture in the United States during the 1970s and the other with various consequences of the farm policies followed during the 1970s. The second session consisted of two papers: one emphasized potential developments in world food production, consumption, trade, and farm policies and how they might affect U.S. agriculture; the other considered possible changes in the structure of U.S. agriculture. The third session was concerned with the future of U.S. farm policy, especially major issues of legislation concerning agricultural policy.
Proceedings of the Conference on Food and Agricultural Policy for the 1980s, held in Washington, D.C., Oct. 2-3, 1980.
Includes bibliographical references.
ne 08/06/2018
Loans
Keywords: Agriculture and state; Food supply